The pedagogical task of designing and developing language teaching materials is a consequent implementation of a language course. Language teachers should be involved in this task by taking into account learning objectives, information processing stage - HAMADA, Hacène (Journal of Human Sciences, 2007)
The pedagogical task of designing and developing language teaching materials is a consequent implementation of a language course. Language teachers should be involved in this task by taking into account learning objectives, information processing stages, and discourse functions, in order to satisfy learning needs. Such a task requires the design of learning activities which encourage learners to develop learning strategies.  Teachers’ commitment in the task of implementation, by developing their own language materials, makes them aware of their role in promoting learners’ strategies. This task, then, provides teachers with autonomy of analysis, selection, design and development of their materials